Perkembangan Batik Sleman - Sri Suryaningsum; Raden Hendri Gusaptono; Sri Luna Murdianingrum; Alifa Nida Maharani; Rakyan Widowati Tanjung (Eksos LPPM, 2020)
This research uses a qualitative analysis approach. Data of this research obtained collected from direct observation of batik motifs, the development process, and batik production in the batik centre of Sleman Regency. The results of the research conducted from January to June 2019 are to find out how the history of batik in Sleman Regency and what its development has been to date. Review the motives and meanings contained in Sleman batik. Batik in Sleman Regency is in the time of growing and developing. Now, Sleman able to develop batik motifs and production with the support of the government, the community, and other institutions. The geographical situation of Sleman consists of lowlands and highlands, giving rise to various batik motifs that occur adapted to their environmental conditions. With the development of time and technology, it also influences the development of the Sleman batik development process. Batik themes in Sleman include the motifs of salak, elephant, and eel. Sleman batik colours tend to be dark because Sleman does not have a coastal area. Sleman Batik Development continues done through batik training. Sleman batik creation contest. The government carries out a cultural festival. Establishment of Small and Medium Industries (IKM). Sleman Batik continues processed into various new products such as bags and others. The government is expected to increasingly supportive the promotion and development of Sleman batik motifs. Maintain ongoing training for batik makers. Incorporating Sleman Batik crafts in local content must be in public and private schools